2013
DOI: 10.1155/2013/756989
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Mechanisms of Neuroglobin’s Neuroprotection

Abstract: Neuroglobin (Ngb) is an oxygen-binding globin protein that has been demonstrated to be neuroprotective against stroke and related neurological disorders. However, the underlying mechanisms of Ngb's neuroprotection remain largely undefined. Mitochondria play critical roles in multiple physiological pathways including cell respiration, energy production, free radical generation, and cellular homeostasis and apoptosis. Mitochondrial dysfunction is widely involved in the pathogenesis of stroke and neurodegenerativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 123 publications
1
58
0
2
Order By: Relevance
“…Notably, a link between Ngb levels and regulation of the c-Fos gene was reported in an earlier study where exacerbated c-Fos response to hypoxia was observed in Ngb knockout mouse, suggesting that Ngb deficiency might sensitize the brain to hypoxic brain injury (Hundahl et al, 2011). Taken together, our new findings are consistent with the scope of previously observed neuroprotective effects of elevated Ngb, as in the majority of reported injury models, the proposed modes of neuroprotection by Ngb have been linked with improved sustenance of mitochondrial function (Yu et al, 2013). The proposed mechanisms by which Ngb might ameliorate mitochondrial function in support of neuronal survival, include involvement in augmentation of respiratory chain function (Kiger et al, 2011; Lechauve et al, 2012), interactions with cytochrome c (Fago et al, 2006; Raychaudhuri et al, 2010; Fiocchetti et al, 2013), preservation of respiratory complex lV activity by sequestration of excessive nitric oxide (Brunori et al, 2005; Singh et al, 2013) as well as neutralization of free radicals (Herold et al, 2004; Fordel et al, 2007; Li et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Notably, a link between Ngb levels and regulation of the c-Fos gene was reported in an earlier study where exacerbated c-Fos response to hypoxia was observed in Ngb knockout mouse, suggesting that Ngb deficiency might sensitize the brain to hypoxic brain injury (Hundahl et al, 2011). Taken together, our new findings are consistent with the scope of previously observed neuroprotective effects of elevated Ngb, as in the majority of reported injury models, the proposed modes of neuroprotection by Ngb have been linked with improved sustenance of mitochondrial function (Yu et al, 2013). The proposed mechanisms by which Ngb might ameliorate mitochondrial function in support of neuronal survival, include involvement in augmentation of respiratory chain function (Kiger et al, 2011; Lechauve et al, 2012), interactions with cytochrome c (Fago et al, 2006; Raychaudhuri et al, 2010; Fiocchetti et al, 2013), preservation of respiratory complex lV activity by sequestration of excessive nitric oxide (Brunori et al, 2005; Singh et al, 2013) as well as neutralization of free radicals (Herold et al, 2004; Fordel et al, 2007; Li et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Ngb has been the focus of avid research efforts for its neuroprotective property that may hold the key to improving outcomes or possibly curing neurological disorders, including stroke and Alzheimer’s disease (Yu et al, 2013). Ngb overexpression in stroke animal models decreased the severity of functional and histological deficits (Khan et al, 2006; Sun et al, 2003; Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This neuroprotective function may stem from its intimate association with mitochondrial function in ATP production, programmed cell death and reactive oxygen species scavenging. The Ngb role in these processes implicates its importance in cellular defense against oxidative stress (Antao et al, 2010; Brunori et al, 2005; Yu et al, 2013). Studies in vitro have shown that human Ngb changed structurally during oxidative stress and functions as an oxidative stress-responsive sensor for neuroprotection (Watanabe et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the possible stimulation of endogenous neuroprotective mechanisms has emerged as a promising strategy [5]. In this context, in the last years, increased attention has been paid to neuroglobin (NGB), an oxygen-binding globin that has been demonstrated to be an endogenous neuroprotective molecule likely related to mitochondrial function and regulation [12]. In the present review article, available evidence on NGB and on the possible mechanisms of action involved in NGB’s neuroprotection, with particular reference to its anti-apoptotic role, will be briefly summarized and discussed.…”
Section: Introductionmentioning
confidence: 99%